Tragedi 1965 dan Krisis Moral (Diskursus Para Saksi Sejarah dalam Terang Sila Kemanusiaan yang Adil dan Beradab) - Agu, Egidius; Yustinus, Yustinus (Jurusan Ilmu Sosial Politik Fakultas Ilmu Sosial Universitas Negeri Padang, 2024)
The focus of this research is to examine the moral position in the 1965 mass killings tragedy in Indonesia. We will explore the ethical debates involving the role of individuals and the government in the incident, as well as its implications for Indonesian society and history. This analysis will help us understand the moral conflicts that influenced the decisions, actions, and impact of this controversial historical period. However, this tragedy remains an unhealed historical wound. This article explores the root causes that led to the 1965 tragedy in Indonesia. The approach used in exploring this tragedy is a qualitative approach by referring to several sources of literature and in the spirit of dialogue with Pancasila as the basis of the Indonesian state. The purpose of the discussion of this paper is first, to find the degradation of moral values from the 1965 mass murder tragedy in Indonesia. Second, to arouse everyone's awareness to foster moral awareness. That morality becomes a light to do good and act justly and at the same time opens the way for him to return to the basis of morality in a pattern of subject-subject relations in order to build civilized humanity.